Axial compressive behavior of partially CFRP confined seawater sea-sand concrete in circular columns – Part II: A new analysis-oriented model. (15th August 2020) - Yang, Junlong; Wang, Jizhong; Wang, Ziru
Abstract: For the comprehensive analysis of the mechanical performance of concrete structures wrapped with partial FRP strips, the development of an accurate and versatile axial stress-strain model is of significant importance. No research, however, has been conducted to present a satisfactory analysis-oriented stress-strain model for partially FRP confined concrete. To this end, this paper firstly investigates the performance of several existing analysis-oriented models in assessing the FRP partially wrapped columns. The results show that all selected models cannot provide reasonable predictions for the test specimens, especially for the specimens possessing strain-softening stress-strain relationships. Therefore, the dilation properties and the peak axial strength expressions of active-confinement base models were both revised based on the test observations and a new analysis-oriented model was proposed for partially FRP confined concrete. Finally, a large database of CFRP partially wrapped columns was assembled through an extensive literature review to evaluate the accuracy of models. By comparing the test results with the predicted calculations, the proposed model can provide accurate and reasonable predictions both for the ultimate conditions and the complete axial stress-strain relationships, which were obviously superior to the other existing models.